A study of relationship between customer and supplier in cutlery outsourcing - Qu, Xinna (2007)
The relationship between customer and supplier has many significant benefits to both parties involved. It is increasingly emphasized by companies within outsourcing activities. Since outsourcing is become more and more important for companies to survive in fierce competitions, the customer and supplier relationship within outsourcing arrangement becomes more crucial. However, establishing and maintaining a successful relationship is not easy. Many outsourcing relationship failures have been observed. This paper aims to examine some important relationship factors as well as attempt to find a practical approach to build up and maintain the customer and supplier relationship successfully in outsourcing activities. Through examining the relationships between a Chinese cutlery factory and its western customers, four relationship construction models were found among which the middleman model is observed to effectively and positively impact on establishing and maintaining the customer and supplier relationship. It is like a super way to get the performance of customer-supplier relationship from zero to a high level. It also helps maintain the relationship. Although the middleman might be removed from the relationship in the future if the two terminal parties do not need it any more, the great positive impact of middleman model on constructing and maintaining relationship before the relationship is totally mature should not be ignored...